Vietnam's Exports to the Chinese Market: Risks and Potential Mitigators. (August 2019) - Binh, Ngo Xuan
From the characteristics of the Chinese market and the current status of Vietnam's exports to this market, this article tries to point out the risks that Vietnamese exporters have to identify in order to find ways to overcome those risks, thereby to help increase exports from Vietnam to the Chinese market which is a very important market of Vietnam. In this article, the author does not focus on the opportunities brought about by the Chinese market or the current status of Vietnamese exports of goods to this market. The aim of the article is mainly to identify the risks that come from the Chinese customers or Chinese trade policy, etc. The intention of the author is to evaluate the risks and current policy practices in order to bring about recommendations for policymakers to deal with the risk involved in current Vietnam–China trade. To achieve the above objectives, the article uses analytical, statistical and comparative methods. These are common methods in economic and business analysis. Research data are collected from primary and secondary sources, that is, the data collected from domestic and international authors, from the general department of statistics, general department of customs and Ministry of Industry and Trade of Vietnam. The article argues that the Chinese market is very important for exports from Vietnam and contains many risks; and that it is imperative to identify these risks. It also considers what the government and enterprises of Vietnam have to do to overcome these risks.